Hydrogen sulfide in plant biology : past and present - Singh, Samiksha, 1985- (Academic Press, 2021)
Hydrogen Sulfide in Plant Biology: Past and Present includes 17 chapters, with topics from cross-talk and lateral root development under stress, to post-translational modifications and disease resistance. With emerging research on the different roles and applications of H2S, this title compiles the latest advances of this key signaling molecule. The development of a plant requires complex signaling of various molecules like H2S in order to achieve regulated and proper development, hence hydrogen sulfide (H2S) has emerged as an important signaling molecule that regulates nearly each and every stage of a plant's lifecycle. Edited by leading experts in the field, this is a must-read for scientists and researchers interested in plant physiology, biochemistry and ecology.